PERANCANGAN APLIKASI ANDROID ABSENSI SISWA PADA SEKOLAH SMK NEGERI 5 PADANG - Rajulianto Rajulianto; Yeka Hedriyani (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
The purpose of this study was to design an application for attendance at the SMK Negeri 5 Padang school which was used as student absenteeism when the teaching and learning activities took place and to see reports of student attendance. The attendance process is carried out by utilizing a smartphone through a client-server based Android application, so that the attendance process no longer takes the timesheet on the picket table and records it on paper. The attendance application design was built using object-oriented programming methods using UML (Unified Modeling Language) modeling, among others: Context Diagrams, Use Case Diagrams, Activity Diagrams and Class Diagrams. On the server side the system is built using PHP (Hypertext Preprocessor) with CSS (Cascading Style Sheets) as an additional language and as an editor using SublimeText, while applications on the client side use the Java Development Kit (JDK) language and use MySQL as a database. The student absentee application at the SMK 5 Padang is produced namely, the application on the server side with a web display that is used for client management, while on the client side will produce an application used to retrieve student attendance data and view student attendance data reports Keywords: Sudent attendence, Android, Client-Server, PHP(Hypertext Preprocessor).